The development of immunosorbents for the treatment of systemic lupus erythematosus via hemoperfusion - Yu, Yameng; Ou, Lailiang (Frontiers in Medicine, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease that involves multiple organ systems and is characterized by elevated levels of autoantibodies and immune complexes. The immunoadsorption technique removes pathogenic toxins from patients' blood through extracorporeal clearance process to alleviate the symptoms of the disease. An immunosorbent is a key component of the immunoadsorption system that determines the treatment's efficacy and safety. Immunosorbents are generally prepared by immobilizing antibodies, antigens, or ligands with specific physicochemical affinities onto a supporting matrix. Immunosorbents and pathogenic toxins bind through affinity adsorption, which involves electrostatic interactions, hydrogen bonds, hydrophobic interactions, and van der Waals forces. Immunosorbents are classified into three categories based on their interaction mechanism with toxins: non-selective, semi-selective, and highly selective. This review aims to summarize the current status of various commercial immunosorbents used to treat SLE. Moreover, recent developments in immunosorbents were briefly discussed in terms of specific ligands and supporting matrix.